Life in the "socialist cities" of the early 1930s - Юлия Косенкова (Проект Байкал, 2023)
The article examines new, previously unresearched archival materials containing the results of a survey conducted in 1936 of four well-known “socialist cities” – new housing developments at large industrial enterprises. The uniqueness of this work lies in the critical approach to the process of implementing in practice of the main urban planning concept, which was formed in the late 1920s in connection with the adopted course of forced industrialization of the country. During the survey, all the components of the concept of “socialist cities” were carefully analyzed, including planning features, typology of housing and principles of “socialization of life”, social composition of the population, departmental affiliation, etc. The boundaries of the implementation of these policies imposed by life itself were revealed, which ultimately led to the actual destruction of the concept. At the same time, the article shows that the authors’ attempts to formulate their own principles of organizing people’s lives, based on the changed “spirit of the times” of the second half of the 1930s, already contained new boundaries of unrealization.